Independent Learning Through Youtube: Puppetry Arts Learning for The Duo Puppeteer Brothers - Amrina Rosyada; Dendi Pratama; Widya Widya (Deiksis, 2022)
As one of the Indonesian honors, puppetry arts are supposed to be socialized and preserved for future generations. It needs creative, interactive, and digital-based media due to the fast and unstoppable global changes. This research aimed to demonstrate the use of YouTube as one of the interesting and interactive media platforms in learning the puppetry arts independently for the duo puppeteer brothers, Prama and Rafi. By applying a qualitative research design with narrative analysis, this research had literally observed, virtually interviewed, and digitally documented a set of questionnaires to the duo puppeteer brothers. Several data were also collected from secondary sources such as YouTube channels and online news. Unlike other little puppeteers who learn the puppetry arts in a studio, the results revealed that the duo puppeteer brothers had never joined any puppetry arts studio. At the age of 16 and 13 years old, they have been learning the puppetry arts through YouTube channels for years to identify different styles of professional puppeteers in performing the puppets’ shows. Using YouTube channels, the duo puppeteer brothers enjoy the puppetry arts learning and could preserve the national noble values and culture.